2011
DOI: 10.1386/jaah.2.2.137_1
|View full text |Cite
|
Sign up to set email alerts
|

Kinesthetic ability and the development of empathy in Dance Movement Therapy

Abstract: This study investigates the relationship between change in kinesthetic ability and the development of empathy in a group of Dance Movement Therapy (DMT) trainees. Art Therapy and Social Science students served as comparison groups. A field study was conducted using a quasi-experimental pre-post control group design. Participants were 62 graduate students. A standard self-report measure of empathy was used, and kinesthetic ability was evaluated using a table of movement dimensions based on Laban Movement Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…For example, it has been found that dancers have higher interoceptive accuracy than individuals without such movement training (Christensen et al, 2018 ), and more skilled dancers provide higher self-reported levels of emotional intelligence (Petrides et al, 2006 ). While these studies do not provide a direct link between movement expertise and increased empathy, the increasing implementation of dance movement therapy in the management of ASD suggests that dance may facilitate the development of empathic behaviours (Behrends et al, 2016 ; McGarry & Russo, 2011 ; Federman, 2011 ; Koch et al, 2015 ; Mastrominico et al, 2018 ). To this end, participants in the McNorm experiments will also complete the Toronto Empathy Scale (Spreng et al, 2009 ), to generate individual trait empathy scores for consideration in the analysis.…”
Section: The Mcnorm Librarymentioning
confidence: 99%
“…For example, it has been found that dancers have higher interoceptive accuracy than individuals without such movement training (Christensen et al, 2018 ), and more skilled dancers provide higher self-reported levels of emotional intelligence (Petrides et al, 2006 ). While these studies do not provide a direct link between movement expertise and increased empathy, the increasing implementation of dance movement therapy in the management of ASD suggests that dance may facilitate the development of empathic behaviours (Behrends et al, 2016 ; McGarry & Russo, 2011 ; Federman, 2011 ; Koch et al, 2015 ; Mastrominico et al, 2018 ). To this end, participants in the McNorm experiments will also complete the Toronto Empathy Scale (Spreng et al, 2009 ), to generate individual trait empathy scores for consideration in the analysis.…”
Section: The Mcnorm Librarymentioning
confidence: 99%
“…In terms of visual arts creation, one study finds that professional visual artists scored higher in emotional sensitivity than the general population (Drevdahl & Cattell, 1958). However, studies examining shorter-term outcomes find null results on empathy among art therapy students (Federman, 2011) and children (Goldstein & Winner, 2012). There are also no effects of group art classes on prosocial behavior (Good & Russo, 2016), and inconsistent results on theory of mind among children (Goldstein & Winner, 2012).…”
Section: Potential Benefits Of Arts Engagementmentioning
confidence: 99%
“…Most studies examine prosocial behavior directed toward one’s own movement partner, but some find that the effects of synchronous movement extend to other targets—to friends of infants’ movement partner (Cirelli, Wan, et al, 2014; Cirelli et al, 2016) and even to outgroup members among adults (Good et al, 2017; Reddish et al, 2016). However, one study found that dance training was associated with fewer aggressive behaviors, but no change in prosocial behaviors (Koshland, 2009), and other studies have found no changes in empathy (Federman, 2011) or theory of mind (Goldstein & Winner, 2011) with dance training. For a review of this research, see Cirelli (2018).…”
Section: Potential Benefits Of Arts Engagementmentioning
confidence: 99%
“…As for kinesthesis, Federman (2011) found an increase in kinesthetic ability among a group of Dance Movement Therapy trainees. Chatzopoulos et al (2018) found that a creative dance program may enhance preschool children's proprioception.…”
Section: Discussionmentioning
confidence: 94%